Sensory Acceptability and Viability of Lactobacillus acidophilus and Lactobacillus bulgaricus in Spent Coffee Ground Candy - Concepcion, Remilyn Vendiola; Barcelon, Eufemio G; Luneta, Janiko Marco (Indonesian Coffee and Cocoa Research Institute, 2025)
Spent coffee ground (SCG) is a residual material considered as waste that remains after brewing coffee. Conventional brewing techniques generate large amount of SGC that is rich in lignocellulose and valuable bioactive compounds that can be exploited as functional food ingredients. This study explored the development of a probiotic SCG candy using spent coffee grounds (SCG) as a sustainable and functional matrix, incorporating Lactobacillus acidophilus and L. bulgaricus. The effect of different carbohydrate sources—banana and potato— on the candy’s physicochemical properties, sensory attributes, and probiotic viability during storage was evaluated. Four formulations were prepared: SCG-only (T0), SCG–banana (T1), SCG–banana/potato (T2), and SCG–potato (T3), each stored at room temperature (25±2 °C) and refrigeration (4 °C) for four weeks. Physico- chemical analyses showed moisture content ranged from 7.49% (T0) to 9.43% (T3), water activity from 0.46 to 0.54, and pH values from 6.87 to 7.61. Total soluble solids (TSS) were between 44.00 and 52.66 °Brix. These parameters remained stable throughout storage. Viable counts of Lactobacillus spp. remained above 8.3 log CFU/g in all samples, with SCG–banana (T1) stored at 4 °C achieving the high- est count of 8.45 log CFU/g after four weeks. Sensory evaluation using a 5-point hedonic scale revealed that SCG–banana (T1) and SCG–banana/potato (T2) achieved significantly higher ratings in chewiness (4.6), mouthfeel (4.6), overall flavor (4.5), and acceptability (4.7) than the control (T0). Refrigerated storage preserved microbial viability and sensory quality better than room temperature. Overall, this study confirms that SCG can serve as a value-added matrix for probiotic delivery in confections. The inclusion of banana improved both functionality and consumer preference, supporting the development of shelf-stable, sustainable, probiotic-rich snacks.